Assessment of heavy metals uptake and translocation by Aquilaria malaccensis planted in soils containing sewage sludge - Sundara Rajoo, Keeren; Abdu, Arifin; Abdul Hamid, Hazandy; Karam Singh, Daljit Singh; Jusop, Shamshuddin; Jamaluddin, Aiza Shaliha; Wong, Wan Zhen (Science Publications, 2013)
Increase in human population has resulted in an enormous growth in the volume of wastewater. The conventional methods of sewage sludge disposal, that is the by-product of wastewater treatment, are costly and not environment-friendly. An ideal way for sewage sludge management is by using it as a soil amendment in agricultural land due to sewage sludge's high organic matter content. However, sewage sludge contains high levels of heavy metals that can be harmful to both plants and the environment. Hence, these metals need to be removed before the sewage sludge is to be used as a soil amendment. The objective of this study was to assess the potential of Aquilaria malaccensis to uptake and translocate heavy metals found in sewage sludge. A.malaccensis seedlings were planted on six different planting media: T0/Control (100% soil), T1 (80% soil and 20% sewage sludge), T2 (60% soil and 40% sewage sludge), T3 (40% soil and 60% sewage sludge), T4 (20% soil and 80% sewage sludge) and T5 (100% sewage sludge) for the duration of 16 weeks. The growth performance of height and basal diameter was measured using diameter tape and venier caliper every two weeks, respectively. The average dry weight biomass of A.malaccensis was measured using destructive sampling at 16 weeks after planting. Plant samples were collected after harvest and soil samples were collected before planting and after harvesting. Atomic Absorbtion Spectrophotometer (AAS) was used to determine the concentration of heavy metals in the planting media and the plant parts (leaves, stem and roots). The highest growth of A.malaccensis was recorded for the T5 growth media. The highest concentration of Fe in the roots of the A.malaccensis plant was in the T5 growth media (2770.75 ppm). The highest accumulation of Zn (95.62 ppm) was recorded in the roots of A.malaccensis in the T5 growth media, whereas the stem of the A.malaccensis in T5 recorded the highest Cd accumulation (3.75 ppm). The highest Pb uptake was recorded in the roots of A.malaccensis in T5 (39.79 ppm), while the lowest accumulation of Pb was noted in the leaves of the A.malaccensis in control (16.08 ppm). The highest Translocation Factor (TF) (2.00) for Cd was recorded in T5. The lowest Bioconcentration Factor (BCF) for Cu was recorded at T5 (0.18). The highest TF for Pb was recorded in control (1.50), while the lowest was in T5 (1.23). The BCF for Zn was lowest in T5 (0.64). The A.malaccensis plant was found to be suitable for taking up heavy metals from sewage sludge especially Cd and Cu. The roots of A.malaccensis are ideal in uptaking and storing Fe, while the stem of the A.malaccensis plant is ideal for the uptake and accumulation of Cd. More studies need to be conducted, especially in field conditions, to optimize the potential of the A.malaccensis plant as a phytoremediator.